The social use of media : cultural and social scientiific perspectives on audience research - Bilandzic, Helena; Patriarche, Geoffroy; Traudt, Paul J. (European communication research and education association (ECREA), 2012)
This collection of essays provides an overview of research on the social uses of media. Drawing on long traditions in both cultural studies and the social sciences, it brings together competing research approaches usually discussed separately. The topics include up-to-date research on activity and interactivity, media use as a social and cultural practice, and participation in a cultural, political, and technological sense. This volume incorporates current audience and reception studies and makes a significant contribution to the development of interdisciplinary approaches to audience and user studies